CHRONIC HEART FAILURE: CLINICAL GUIDELINES AND REAL CLINICAL PRACTICE - E. K. Shavarova; L. A. Babaeva; S. S. Padaryan; N. N. Soseliya; O. I. Lukina; A. S. Milto (Рациональная фармакотерапия в кардиологии, 2017)
Aim. Expert assessment of real clinical practice compliance with national guidelines on management of patients with chronic heart failure (HF) before the opening of the Expert Center of HF treatment.Material and methods. All patients admitted to 2 city clinical hospitals of Moscow with HF were included into the register. Clinical, demographic, laboratory and instrumental characteristics and medical treatment before and during hospitalization were evaluated, as well as recommendations contained in the discharge summary.Results. 300 patients with HF were included into the register. The mean age was 75 years (39, 95); the proportion of men – 44%. 95% of patients had HF IIIV (NYHA), among them 24% HF II, 61% HF III, 15% HF IV (NYHA). HF with reduced ejection fraction (HFrEF) was found in 45% of patients. 22% of the patients did not receive medical treatment before admission. 34% of patients with HFrEF received ACE inhibitors/angiotensin receptor blockers (ARBs), of which only 23% in effective dose. β-blockers were prescribed in 41% of HFeEF patients, of which 22% in the target dose. A third of patients needed in mineralocorticoid receptor antagonists (MRA) received spironolactone. During hospitalization 81% of HFrEF patients received ACEI therapy, 12% – ARBs, 91% – β-blockers, 90% – MRA, 81% – loop diuretics and 13% – thiazide diuretics. According to the discharge summary 5% of patients did not receive post-discharge blocker of the renin-angiotensin-aldosterone system without explanation in the medical documentation. β-blocker with proven efficacy was prescribed to 70% of HFrEF patients. Spironolactone was recommended after discharge in 89% of HFrEF patients.Conclusion. Implementation of register of hospitalized patients with HF gives an opportunity to identify shortcomings in the provision of medical care both in outpatient and inpatient stages.